The natural course of cystic pancreatic neuroendocrine tumours in MEN1 - Eline N M van Vliembergen; Carolina R C Pieterman; Annenienke C van de Ven; Arthur J A T Braat; Gerlof D Valk; Joanne M de Laat (Endocrine Oncology)
Pancreatic neuroendocrine tumours (PanNETs) significantly impact life expectancy in multiple endocrine neoplasia type 1 (MEN1). Both solid and cystic pancreatic lesions are observed in MEN1, yet limited research has been focused on cystic lesions in MEN1. While solid PanNETs are generally considered to have an indolent course, the natural course of cystic lesions remains unclear. This study aims to provide more insights into the natural course of cystic PanNETs in MEN1. Patients with MEN1 and radiologically suspected PanNETs, treated at UMC Utrecht and Radboudumc between 2010 and 2023, were included. In the first part, we examined the characteristics of patients with tumours visible on imaging scans. In the second part, we investigated outcomes of pathological examinations, following resection of these lesions. A total of 136 patients were included, comprising 60 men and 76 women. The median follow-up was 5.1 years. [68Ga]Ga-DOTATOC PET/CT scans showed that both cystic and solid lesions demonstrated [68Ga]Ga-DOTATOC PET/CT uptake. The median growth of cystic and solid PanNETs was similar. Pathological examination of 38 resected tumours confirmed that cystic lesions identified on imaging were indeed PanNETs. Cystic lesions had a median diameter of 26 mm at the time of resection, compared to 18 mm for solid lesions, with comparable Ki-67 indices and mitotic counts. We conclude that cystic and solid PanNETs in MEN1 patients appear to be morphological variations of the same entity, suggesting that similar management approaches should be considered.